Development Of Student Teaching Materials Using An Inquiry Approach Oriented On Critical Thinking Ability In Service Company Accounting Courses - Pertiwi, Indah; Yulyanah; Masitoh, Lisda Fitriana (IJESS International Journal of Education and Social Science, 2024)
University is a continuation of secondary education which is organized to prepare students to become members of society who have academic and professional abilities who can apply, develop and create science, technology and the arts. Learning in higher education is not just about providing material on a particular topic but must also provide a learning experience that enables the development of student independence in learning so that it can improve student learning achievement. There are several obstacles in studying Service Company Accounting in the D3 Accounting Study Program at Pamulang University, including: (1) lecturers are still the main source for learning accounting; (2) the books used by students are inadequate for a conducive learning process; and (3) students find it difficult to understand the contents of the available textbooks so that students' motivation to learn becomes less. Apart from that, based on the results, students' critical thinking abilities are still low. This is what prompted researchers to prepare Student Teaching Materials (BAM) using an inquiry approach oriented towards thinking skills in the hope that it will make it easier for students to learn Service Company Accounting. The aim of this research is to produce Student Teaching Materials (BAM) using an inquiry approach oriented towards thinking skills using an inquiry approach oriented towards critical thinking skills in quality Service Company Accounting lectures based on the aspects: (1) validity, (2) practicality, and (3) ) effectiveness.. This research is a type of research and development. The development in this research is the development of Student Teaching Materials (BAM) using an inquiry approach oriented towards thinking skills using an inquiry approach oriented towards critical thinking skills in Service Company Accounting lectures. The development model used in this research is the Borg & Gall development model. Theoretically, the results of this research will improve students' critical thinking skills and the resulting products can be used in Service Company Accounting lectures.